Contemporary breeding biology of critically endangered Regent Honeyeaters: implications for conservation. (22nd September 2018) - Crates, Ross; Rayner, Laura; Stojanovic, Dejan; Webb, Matthew; Terauds, Aleks; Heinsohn, Robert
Abstract : Identifying factors influencing the demographics of threatened species is essential for conservation, but a lack of comprehensive demographic data often impedes the effective conservation of rare and mobile species. We monitored breeding of critically endangered and semi‐nomadic Regent Honeyeaters Anthochaera phrygia (global population c . 100 pairs) over 3 years throughout their range. Overall nest success probability (0.317) was highly spatially variable and considerably lower than previous estimates for this (and many other honeyeater) species, as was productivity of successful nests (mean 1.58 juveniles fledged). Nest surveillance revealed high predation rates by a range of birds and arboreal mammals as the primary cause of nest failure. An estimated 12% of pairs either failed to establish a territory or their nests did not reach the egg stage. We also found a male bias to the adult sex ratio, with an estimated 1.18 males per female. Juvenile survival for the first 2 weeks after fledging was high (86%). Management interventions that aim to increase nest success in areas of low nest survival must be investigated to address an apparent decline in reproductive output and avoid extinction of the Regent Honeyeater. We show that temporal and spatial variation in the breeding success of rare and highly mobile species can be quantified with robust population monitoring using sampling regimens that account for their life histories. Understanding the causes of spatio‐temporal variation in breeding success can enhance conservation outcomes for such species through spatially and temporally targeted recovery actions.